Short-Term Efficacy Versus Long-Term Maintenance of Pelvic Floor Muscle Training for Perinatal Urinary Incontinence: A Meta-Analysis of Randomized Controlled Trials - Qonita Prasta Agustia; Rahajeng (HM Publisher, 2026)
Background: Postpartum urinary incontinence remains a prevalent, profoundly debilitating complication following childbirth, significantly reducing maternal physical function and psychosocial quality of life. Pelvic floor muscle training is globally established as a conservative first-line treatment. However, the stark contrast between its immediate postnatal efficacy and its long-term maintenance remains inadequately synthesized in the current literature. The aim was to evaluate this chronological divergence. Methods: A systematic review and meta-analysis of randomized controlled trials was conducted. Data were extracted from eligible trials assessing pregnant and postpartum women undergoing pelvic floor muscle training compared to standard care. Primary outcomes included the prevalence and severity of urinary incontinence evaluated at short-term (under one year) and long-term (over one year) intervals. Data were pooled utilizing a random-effects model, calculating risk ratios for dichotomous prevalence data and standardized mean differences for continuous severity scores. Results: Eight randomized controlled trials encompassing over two thousand participants were included. Short-term analysis demonstrated a highly significant reduction in urinary incontinence prevalence among women receiving the intervention (Pooled Risk Ratio 0.65, 95% Confidence Interval 0.52 to 0.81, P < 0.001) and a significant improvement in severity scores (Standardized Mean Difference -0.72, 95% Confidence Interval -0.95 to -0.49, P < 0.001). Conversely, long-term follow-up data evaluated at the seven-year milestone showed a completely diminished effect, with no statistically significant difference in urinary incontinence prevalence between the prior intervention and control groups (Pooled Risk Ratio 0.92, 95% Confidence Interval 0.78 to 1.08, P = 0.45). Conclusion: Structured pelvic floor muscle training provided substantial, rapid short-term efficacy in preventing and treating perinatal urinary incontinence. However, the initial anatomical and neuromuscular gains did not translate into long-term maintenance, highlighting a critical drop-off in behavioral adherence and the necessity for lifelong continuous booster interventions.